2019
DOI: 10.1007/s40544-019-0268-4
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in friction and lubrication of graphene and other 2D materials: Mechanisms and applications

Abstract: Two-dimensional materials having a layered structure comprise a monolayer or multilayers of atomic thickness and ultra-low shear strength. Their high specific surface area, in-plane strength, weak layer-layer interaction, and surface chemical stability result in remarkably low friction and wear-resisting properties. Thus, 2D materials have attracted considerable attention. In recent years, great advances have been made in the scientific research and industrial applications of anti-friction, anti-wear, and lubr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
129
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 280 publications
(138 citation statements)
references
References 123 publications
8
129
0
1
Order By: Relevance
“…As illustrated in Figure a–d, three domains (SLG, BLG, and Cu) showing different friction responses in each panel can be clearly distinguished. Friction forces of both SLG and BLG domains are much smaller than that of bare copper substrate since an ideal graphene film is atomically smooth and has no dangling bond, resulting in low shear strength . Friction force of SLG is larger than that of BLG, which is consistent with previous literature .…”
Section: Resultssupporting
confidence: 90%
“…As illustrated in Figure a–d, three domains (SLG, BLG, and Cu) showing different friction responses in each panel can be clearly distinguished. Friction forces of both SLG and BLG domains are much smaller than that of bare copper substrate since an ideal graphene film is atomically smooth and has no dangling bond, resulting in low shear strength . Friction force of SLG is larger than that of BLG, which is consistent with previous literature .…”
Section: Resultssupporting
confidence: 90%
“…The lubricants are far from perfect, and the service life of conventional lubricants is limited. Therefore, scholars have been looking for high‐performance, environmentally friendly lubricants, [ 2,6 ] and found that lubricant additives [ 7 ] are an effective way to improve performance. [ 8 ] However, current lubricant additives contain several harmful elements which it would be beneficial to remove.…”
Section: Introductionmentioning
confidence: 99%
“…They have the characteristics of large specific surface area, high in‐plane strength, weak interlayer interaction and good surface chemical stability, and thus have very low friction and wear‐resisting properties. Therefore, 2D materials [ 6,15,16 ] have attracted considerable attention. Numerous efforts have been devoted to the design of materials and surfaces to effectively control friction and wear, from nanoscale to macroscopic scale‐graphene, hexagonal boron nitride, molybdenum disulfide, and so forth.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to the relationship between graphite and graphene, the GrF platelets also can be exfoliated to fluorographene (FG) nanosheets with several layers. FG, as the youngest graphene based derivative and the thinnest transparent insulator, exhibits similar properties to GrF but has a smaller size and larger specific surface area compared with GrF, which makes FG an excellent advanced material in many areas, such as solid lubricants, super hydrophobic oleophobic coatings, optoelectronic and thermoelectric devices, electrode materials and so on. The unique properties of FG are caused by the fluoride atoms introduced on the surface of carbon, which changes the hybridization of carbon from sp 2 to sp 3 and increases the interlamellar space in the FG nanosheets .…”
Section: Introductionmentioning
confidence: 99%